2021
DOI: 10.12688/f1000research.28045.2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against hepatitis B virus in hemodialysis patients: trends in dialysis centers of Northern Pakistan

Abstract: Background: Chronic kidney disease (CKD) patients, especially those on hemodialysis, are at increased risk of developing hepatitis B virus (HBV) infection. Guidelines suggest that all patients with CKD should be vaccinated against HBV, but these guidelines are usually not followed. We conducted this study to know the status of vaccination against HBV in CKD patients on regular hemodialysis. Methods: This observational descriptive study was conducted at the Department of Medicine, Sheikh Khalifa Bin Zayed Teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…patients were vaccinated in a study conducted in Pakistan (Nadeem et al, 2021). Besides preventing transmission in the dialysis unit, successful Hepatitis B vaccination also allows for renal transplantation recipient from an anti-HBc positive donor (Holt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…patients were vaccinated in a study conducted in Pakistan (Nadeem et al, 2021). Besides preventing transmission in the dialysis unit, successful Hepatitis B vaccination also allows for renal transplantation recipient from an anti-HBc positive donor (Holt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread HBV vaccine use since 1982 with a clear benefit to Hepatitis B vaccination in CKD patients -in particular the immunocompromised HD patients who are at higher risk of the infection due to frequent blood exposure and skin breaches -there have been limited published studies on vaccination implementation strategies and clinical practice guidelines (Mysore, 2021). Vaccination regime variations and a lack of optimal policy between countries continues to be recognised in recent literature (Haddiya, 2020;Nadeem et al, 2021). Although the CDC guidelines strongly recommend all CKD patients should be vaccinated against HBV, studies have shown the range of CKD patients vaccinated to vary greatly, between 20-73.1%: 20% in Pakistan (Nadeem et al, 2021); 31% in Belgium (Boey et al, 2020); 46% in the UK (Ray et al, 2002); and 73.1% in the US (Ayoola et al, 2019).…”
Section: Clinical Practice Guidelines In Hepatitis B Vaccination In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) imposes a giant fitness burden globally, with a multitude of headaches affecting patients, including an increased susceptibility to infectious diseases. Among those, hepatitis B virus (HBV) contamination provides a considerable risk, especially in people undergoing hemodialysis (Nadeem et al, 2021;Shrestha et al, 2021). The problematic interaction among compromised renal characteristics and immune system changes in CKD sufferers underscores the importance of exploring the effectiveness of hepatitis B vaccination on this precise population (Shrestha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%